NOx degradation in a continuous large-scale reactor using full-size industrial photocatalytic tiles. Issue 7 (25th November 2015) - Bianchi, C. L.; Pirola, C.; Galli, F.; Vitali, S.; Minguzzi, A.; Stucchi, M.; Manenti, F.; Capucci, V.
Abstract : A gas-flow photoreactor working with a UV-A lamp or under direct sunshine to test materials of large size. Abstract : Many reactors were proposed to investigate the efficiency of photocatalytic materials in the degradation of NO x, but the operative conditions are often very far from reality: the parameters and the reactor set-up, which are good for laboratory tests, cannot verify the real efficiency of a photocatalytic material in a real context. To solve this issue, we experimented for the first time with a new kind of gas-flow reactor able to test photocatalytic building materials of large size, optimizing the reaction conditions in order to work both under artificial conditions of irradiation (UV-A lamp) and under direct sunshine.